The BALANCED SCORECARD: SEBUAH BIBLIOGRAFI DARI BERBAGAI PERSPEKTIF - Rindy Dwi Ladista (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
One model of the performance measurement system is the Balanced scorecard. The concept of the Balanced Scorecard was developed by Robert S. Kaplan and David P. Norton in 1992. There have been many articles from research related to the balanced scorecard. This study aims to determine the characteristics of articles with the theme of balance scorecard discussion. This research is a qualitative research using a bibliographic study that refers to the charting the field method. Total of 27 articles from the years 2011-2021 were obtained by accessing the open access website from www.scimagojr.com. The sample is then classified based on the bibliographic data of each article, namely the name of the journal, quartile scopus classification, title, author's name, number of authors, year of publication, research objectives, topic, type, data collection technique, and number of references. The results of this study show that 2014 was the year the most articles of this sample were published. Qualitative research with the topic of consequences and using documentation techniques dominates the research results.